Monitoring, accounting and enforcement in emissions trading regimes - Sonja Peterson (Greenhouse gas emissions trading and project-based mechanisms: OECD Global Forum on Sustainable Development: Emissions Trading, CATEP Country Forum, 2004)
In the past few years permit trading has become a popular policy instrument to achieve emissions reductions or other environmental goals at minimal cost. There are already a number of existing regimes on firm as well as on national level in which permits for SO2, NOX and CO2 emissions but also fishing quotas or water rights are traded. In addition European CO2 emissions trading is expected to start in 2005 and international emissions trading is also planned for the Annex B countries of the Kyoto Protocol. Experience has shown though that permit trading can only be an efficient instrument if emissions and permit trades are monitored and accounted appropriately and if compliance is enforced by those running the programs. Or, as Tietenberg (2001) puts it: ?regardless of how well any tradable permit system is designed, non-compliance can prevent attainment of its economic, social and environmental objectives?.
Keywords: 330; Projektbewertung; Umweltbelastung; Welt